Institutional Learning in North–South Partnerships: Critical Self-Reflection on Collaboration Between Finnish and Tanzanian Academics. Issue 2 (3rd May 2020) - Kontinen, Tiina; Nguyahambi, Ajali M.
Abstract: Knowledge production and its possibilities and pitfalls in North–South research partnerships have gained increasing attention. The previous literature has identified certain pervasive challenges, and suggested a variety of ways to change partnerships, ranging from improvement of current collaboration activities to fundamental transformation of the hegemonic Eurocentric criteria for knowledge. Against this backdrop, we ask what kinds of learning can take place in research partnerships. We draw from two sources – an institutional approach and a classical categorization of learning proposed by Gregory Bateson – to develop a heuristic for analyzing institutional learning in North–South research partnerships. Moreover, based on previous empirical studies and our own experience with academic collaboration between Finnish and Tanzanian scholars, we reflect on the ways in which learning in its different forms shows in partnership practices that need to deal with different, intertwined institutional fields.